The ileocecal valve in transabdominal ultrasound Part 1: Sonographic anatomy and technique - Smereczyński Andrzej; Kołaczyk Katarzyna; Goncerz Grzegorz (Journal of Ultrasonography)
The ileocecal valve is a part of the gastrointestinal tract that separates two intestinal segments differing in both anatomy and function. Dysfunction or surgical removal of the valve usually results in the development of small intestinal bacterial overgrowth syndrome. The available literature lacks a broader discussion and ultrasound presentation of the ileocecal valve. The aim of this study is to present our experience in transabdominal ultrasound of the ileocecal valve in comparison with colonoscopic and computed tomography colonography data. In this part of the manuscript, we discuss the anatomical structures in the right iliac fossa that make up the ileocecal segment of the intestine. The ileocecal valve, which comes in two morphological forms: labial and papillary, is its central part. As shown in computed tomography colonography, the first type is more common, accounting for 76%, the second type accounts for 21%, whereas ileocecal valve lipomatosis is found in 3% of cases. Post-mortem studies have shown a significantly higher incidence of valve lipomatosis, which was found in up to 4 out of 5 cases. Our observations correspond with these findings. Ileocecal valve lipomatosis presents on ultrasound as a hyperechoic, well-circumscribed lesion, with no evident vascularity on color Doppler. This image should be differentiated especially from a lipoma, a relatively common large intestinal pathology. The paper presents two methods of preparation for an ultrasound scan (i.e. only on an empty stomach or after cleansing the intestine) and determines the optimal imaging methods for the ileocecal valve using transabdominal ultrasound. At the end of the ileocecal examination, it should be remembered to assess the lymph nodes in the right iliac fossa.